3-Sulfopropyl methacrylate based cryogels as potential tissue engineering scaffolds. (5th December 2020) - Yürük Durukan, Adile; Işoğlu, Ismail Alper
ABSTRACT: In this study, we developed cryogels containing 3-sulfopropyl methacrylate (SPMA) and 4-vinyl pyridine (4-VP) as a potential scaffold for tissue engineering applications. Cryogels with varying monomer ratios were synthesised by chemical cross-linking under cryogelation conditions. Effect of initiators and cross-linker amount (0.025–0.15 g MBA; 0.012–0.05 g APS; 2.5–12.5 µl TEMED) and also freezing temperature (−20 and −80ºC) were investigated, and the conditions were optimised according to the morphological structures examined by SEM. The functional groups of the materials were characterised by FT-IR. Compression test and swelling were applied to investigate mechanical properties and water absorption ability, respectively. As a preliminary study, selected materials were tested for cell cytotoxicity with MTT. According to our results, the ionic and biocompatible cryogels prepared in this study possessing a highly porous and interconnective structure with good mechanical characteristics and swelling properties can be suitable as tissue scaffolds for many applications.